A short-term high-temperature high-strength titanium alloy and its preparation method and application

By adding Y and Nb elements to Ti-Al-Sn-Zr-Mo-Si-W alloys and casting them using a high-vacuum suspension smelting furnace, the problem of sudden drop in mechanical properties of titanium alloys under short-term high temperature conditions of 700℃ and above is solved, and a high-temperature and high-strength titanium alloy material is realized, meeting the needs of the aerospace field.

CN116144982BActive Publication Date: 2025-03-25HEBEI UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310243967.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-14
Publication Date
2025-03-25
Estimated Expiration
2043-03-14

AI Technical Summary

Technical Problem

The mechanical properties of existing titanium alloys have dropped sharply under short-term high temperature conditions of 700℃ or above, and the degree of surface oxidation has intensified, resulting in deterioration of comprehensive performance, making it difficult to meet the demand for high-temperature and high-strength materials of aerospace vehicles.

Method used

By adding Y elements and Nb elements to Ti-Al-Sn-Zr-Mo-Si-W alloys, casting was performed using a multi-alloyization method and a high-vacuum suspension smelting furnace, the high-temperature strength and oxidation resistance of the alloy at 700°C or higher was significantly improved.

Benefits of technology

It has achieved short-term high-temperature and high-strength use of titanium alloys at 700-750℃, improved the high-temperature tensile strength and elongation of the alloy, reduced the high-temperature oxidation and weight gain, and met the demand for high-temperature high-strength materials in the aerospace field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004125411270000141
    Figure BDA0004125411270000141
  • Figure BDA0004125411270000142
    Figure BDA0004125411270000142
  • Figure BDA0004125411270000151
    Figure BDA0004125411270000151
Patent Text Reader

Abstract

The present invention discloses a short-term high-temperature high-strength casting titanium alloy, the composition of which includes, by mass percentage, 4.0-5.0% Al, 2.0-3.0% Sn, 3.0-6.0% Zr, 0.1-1.5% Mo, 0.35-0.45% Si, 0.5-1.5% W, 0.5-2.0% Nb, 0.1-0.5% Y and unavoidable impurity elements in the titanium alloy with a content not exceeding 0.1%, and the remainder Ti. The present invention adopts a high-vacuum suspension melting furnace equipped with a water-cooled copper crucible for melting and pouring, and the obtained casting high-temperature titanium alloy has a tensile strength of not less than 600MPa and 500MPa at high temperatures of 700°C and 750°C, respectively; after isothermal oxidation for 120h, the oxidation weight gain does not exceed 0.5mg / cm 2 and 0.9mg / cm 2 The present invention improves the thermal strength of the short-time cast high-temperature titanium alloy and can meet the instantaneous high-temperature strength requirement under the application condition of 700°C to 750°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of titanium alloy materials, and specifically relates to a short-term high-temperature high-strength titanium alloy and a preparation method and application thereof, and particularly relates to a short-term high-temperature high-strength cast Ti-Al-Sn-Zr-Mo-Si-W-Nb-Y alloy and a preparation method and application thereof. Background Art

[0002] High-temperature titanium alloys have a series of advantages such as light weight, high strength, corrosion resistance, high temperature resistance, and small linear expansion coefficient. They are widely used in the aerospace field, such as in aircraft shells, fuselage frames, skins, landing gears, stringers, heat shields, and aircraft engines, with significant weight reduction effects. As aerospace vehicles develop towards high Mach flight speeds, in addition to requiring titanium alloys to have low density and high strength, they are also required to withstand higher temperatures and have better forming and processing properties. The highest service temperature of high-temperature titanium alloys currently used for a long time can reach 600°C, and they are all deformable high-temperature titanium alloys. Typical grades include the United States' Ti-1100, the United Kingdom's IMI834, Russia's BT36, and my country's Ti60, Ti600, and TG6.

[0003] In recent years, hypersonic vehicles have become a key area of ​​competition for countries around the world. Because they travel at speeds exceeding Mach 5, the requirements for titanium alloys used as structural materials have also increased in terms of high temperature strength, creep resistance, oxidation resistance, and service temperature. When aircraft fly at these speeds, the intense air friction in the atmosphere generates extremely high heat, causing surface material temperatures to remain at 700°C for a short period (0.5-2 hours), potentially severely impacting the structural integrity of the aircraft or missile. However, the tensile strength of the aforementioned 600°C deformable high-temperature titanium alloy at 700°C is only around 300 MPa, which is difficult to meet operational requirements. The limited literature currently available on short-term high-temperature titanium alloys at 700°C and above focuses primarily on deformation and powder metallurgy preparation methods, which are unable to meet the development trend of large-scale, thin-walled curved surfaces, variable thickness, and integrated structures for titanium alloy components. There is also significant potential for performance improvement. For example, the tensile strength of Ti750 alloy at 750°C is 323 MPa.

[0004] Patent application number 201410810252.0 discloses a yttrium-modified TB2 titanium alloy. Specifically, the invention involves adding rare earth element Y to the TB2 titanium alloy and performing an alloying treatment. This allows impurity elements such as C, O, N, and H, which tend to accumulate at grain boundaries, to react with the rare earth element Y to form rare earth refractory materials. This effectively reduces the distribution of impurity elements at the grain boundaries and, to a certain extent, resolves the grain boundary weakening problem caused by impurity elements such as C, O, N, and H, thereby improving the room-temperature mechanical properties of the TB2 titanium alloy. Although the invention improves the room-temperature mechanical properties by purifying the matrix and reducing the alloy's grain boundary weakening by adding yttrium, it is not suitable for environments requiring high-temperature resistance and high-strength performance.

[0005] Patent application number 201610378836.4 discloses a high-strength tungsten-containing titanium alloy. By adding an appropriate amount of the element W to the Ti-Al-Mo-Cr alloy system, the alloy achieves a tensile strength of 860 MPa to 1500 MPa after annealing, achieving a good balance of strength, ductility, and toughness within a wide adjustable range. However, the alloy is produced through deformation processing rather than casting, and therefore cannot meet the low-cost and dimensional requirements of large structural components.

[0006] Patent application number 201610478787.1 discloses a multi-component solid solution-strengthened heat-resistant titanium alloy. This multi-component solid solution strengthening imparts excellent strength and plasticity at both room and high temperatures. Its operating temperature is higher than that of conventional Ti-Al-Sn-Zr-Mo-Si heat-resistant alloys, allowing for long-term use at temperatures up to 650°C. However, its short-term high-temperature use, particularly at temperatures above 700°C, is limited.

[0007] Patent application number 201310431900.7 discloses a method for producing titanium alloy blades using investment casting, including the following steps: preparing an alloy according to a specific ratio, melting and pouring the alloy at a melting temperature of 1790°C and a pouring temperature of 1710°C; then demolding the resulting blade, heat treating it, and then surface treating it to produce the titanium alloy blade. Although the investment casting method produces a titanium alloy blade with a strength of 1200 MPa, it is not capable of withstanding temperatures of 700°C or above.

[0008] Therefore, it is crucial to provide a titanium alloy that can be used at high temperatures of 700°C or above for a short time and has large component sizes, thin-walled curved surfaces, and variable thickness. Summary of the Invention

[0009] In response to the above problems, the first purpose of the present invention is to provide a high-temperature, high-strength cast Ti-Al-Sn-Zr-Mo-Si-W-Nb-Y titanium alloy that can be used at temperatures of 700°C and above (700-750°C) for a short time (0.5-2h), so as to solve the problem that the mechanical properties of existing titanium alloys drop sharply when the operating temperature exceeds 700°C in a short period of time, and the degree of surface oxidation is seriously aggravated, which leads to a sharp deterioration in comprehensive performance.

[0010] A second objective of the present invention is to provide a method for preparing the aforementioned short-term high-temperature, high-strength cast titanium alloy. This method utilizes a multi-component alloying process to significantly improve the alloy's high-temperature strength at temperatures of 700°C or higher while also maintaining its high-temperature oxidation resistance. This method utilizes the most common casting method, rather than deformation processing, to produce alloy components. The resulting castings meet component requirements and reduce manufacturing costs.

[0011] The third purpose of the present invention is to provide an application of the above-mentioned short-term high-temperature high-strength cast titanium alloy, which is mainly used for the production of external shells of aerospace vehicles based on its short-term high-strength performance at 700-750°C, rather than the general titanium alloy used for compressor discs of engine blades.

[0012] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0013] In a first aspect, the present invention provides a short-term high-temperature high-strength titanium alloy, wherein the components of the titanium alloy include, by mass percentage, 4.0-5.0% (e.g., 4.1%, 4.3%, 4.5%, 4.7%, 4.9%, 5.0%) of Al, 2.0-3.0% (e.g., 2.25%, 2.50%, 2.75%, 3.0%) of Sn, 3.0-6.0% (e.g., 3.2%, 4.0%, 5.0%, 5.8%, 6.0%) of Zr, 0.1-1.5% (e.g., 0.3%, 0.8%, 1. 2%, 1.5%) of Mo, 0.35-0.45% (such as 0.37%, 0.4%, 0.42%, 0.45%) of Si, 0.5-1.5% (such as 0.7%, 1.0%, 1.3%, 1.5%) of W, 0.5-2.0% (such as 0.7%, 1.0%, 1.5%, 1.8%, 2.0%) of Nb, 0.1-0.5% (such as 0.15%, 0.2%, 0.3%, 0.4%, 0.45%, 0.5%) of Y, and the remainder of Ti and unavoidable impurities.

[0014] The Ti-Al-Sn-Zr-Mo-Si-W-Nb-Y alloy of the present invention adds Y and Nb to the Ti-Al-Sn-Zr-Mo-Si-W alloy. The combined effects of these elements influence the alloy's microstructure and structure, thereby increasing the alloy's operating temperature and significantly improving its high-temperature strength at temperatures of 700°C or higher while also maintaining its high-temperature oxidation resistance, enabling short-term high-temperature, high-strength use. The addition of Y enhances the chemical activity of the alloy melt, reduces the melt's specific interfacial energy, and thus reduces the nucleation work, thereby increasing the nucleation rate and making the original β-Ti grain size more uniform. The pinning effect of the Y2O3 phase formed by the combination of Y and oxygen strengthens the grain boundaries, hinders grain boundary motion at high temperatures, and improves the alloy's high-temperature properties. Furthermore, the Y2O3 phase induces the formation of parallel α / β lamellae along the grain boundaries, reducing grain distortion energy. The addition of Nb further refines and homogenizes the alloy structure, promoting the precipitation of silicides on the residual β-Ti. At room temperature, silicides act on the α and residual β phases of Ti, improving the alloy's tensile properties. At high temperatures, silicides act on the α / β and residual β phase grain boundaries of Ti, as well as on β grain boundaries, reducing the weakening of grain boundaries caused by high temperatures and also altering the alloy's oxide morphology. However, the addition of more Nb is not necessarily better. Excessive Nb content leads to larger silicides, reducing alloy properties, and the Nb addition range decreases with increasing temperature. The continuous solid solution of Nb and Zr reduces the solubility of Si and Sn, promoting the precipitation of silicides in the β-Ti phase and the precipitation of tin-rich phases. Due to the small size of the precipitated particles, they play a certain role in dispersion strengthening in the alloy, thereby improving the mechanical properties of the alloy. This significantly improves the alloy's high-temperature strength at temperatures of 700°C or higher while also taking into account its high-temperature oxidation resistance, allowing it to be used at high temperatures and strength for short periods of time.

[0015] Preferably, the titanium alloy comprises the following components in mass percentage: 4.2-5.0% (e.g., 4.2%, 4.5%, 4.7%, 4.9%, 5.0%) of Al, 2.65-3.0% (e.g., 2.75%, 2.85%, 2.95%, 3.0%) of Sn, 3.0-6.0% (e.g., 3.2%, 4.0%, 5.0%, 5.8%, 6.0%) of Zr, 0.6-1.5% (e.g., 0.7%, 0.8%, 1.0%, 1.2%, 1.5%) of Zr. The composition includes the following: 1.5% Mo, 0.35-0.45% (such as 0.37%, 0.4%, 0.42%, 0.45%) Si, 0.8-1.5% (such as 0.9%, 1.0%, 1.3%, 1.5%) W, 0.5-2.0% (such as 0.7%, 1.0%, 1.5%, 1.8%, 2.0%) Nb, 0.1-0.5% (such as 0.15%, 0.2%, 0.3%, 0.4%, 0.45%, 0.5%) Y, and the remainder Ti and unavoidable impurities.

[0016] Preferably, the titanium alloy comprises the following components in mass percentage: 4.5-5.0% (e.g., 4.6%, 4.7%, 4.8%, 4.9%, 5.0%) of Al, 2.65-2.85% (e.g., 2.7%, 2.75%, 2.8%, 2.85%) of Sn, 3.0-6.0% (e.g., 3.2%, 4.0%, 5.0%, 5.8%, 6.0%) of Zr, 0.8-1.5% (e.g., 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%) of Zr, )% (e.g., 0.41%, 0.42%, 0.43%, 0.44%, 0.45%) of Mo, 0.4-0.45% (e.g., 0.41%, 0.42%, 0.43%, 0.44%, 0.45%) of Si, 0.8-1.2% (e.g., 0.9%, 1.0%, 1.1%, 1.2%) of W, 0.5-2.0% (e.g., 0.7%, 1.0%, 1.5%, 1.8%, 2.0%) of Nb, 0.1-0.4% (e.g., 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%) of Y, and the remainder of Ti and unavoidable impurities.

[0017] Preferably, the raw materials of the titanium alloy are selected as follows: sponge titanium with a purity of 99.8%, sponge zirconium with a purity of 99.4%, Al block with a purity of 99.7%, Y block with a purity of 99.9%, Sn block with a purity of 99.9%, Mo block with a purity of 99.95%, Nb block with a purity of 99.95%, Si block with a purity of 99.5%, and Ti-90W master alloy.

[0018] Preferably, the room temperature tensile strength of the titanium alloy is not less than 1000 MPa (e.g., 1010 MPa, 1030 MPa, 1050 MPa, 1070 MPa, 1100 MPa, 1200 MPa), and the elongation is not less than 2.5% (2.6%, 2.8%, 3.5%, 4.5%, 5.5%). The room temperature tensile strength is measured at an experimental test temperature of 10 to 35°C.

[0019] Preferably, the tensile strength of the titanium alloy at 700° C. is not less than 600 MPa (e.g., 645 MPa, 660 MPa, 680 MPa, 720 MPa, 800 MPa, 1000 MPa, 1200 MPa).

[0020] Preferably, the tensile strength of the titanium alloy at 750° C. is not less than 500 MPa (e.g., 525 MPa, 540 MPa, 560 MPa, 580 MPa, 600 MPa, 700 MPa, 800 MPa, 1000 MPa, 1200 MPa).

[0021] Preferably, the titanium alloy has an oxidation weight gain of no more than 0.5 mg / cm after oxidation at 700°C for 120 hours. 2 (e.g. 0.45 mg / cm 2 , 0.4mg / cm 2 , 0.35mg / cm 2 , 0.3mg / cm 2 , 0.25mg / cm 2 , 0.1mg / cm 2 ).

[0022] Preferably, the titanium alloy undergoes oxidation weight gain of no more than 0.9 mg / cm after oxidation at 750°C for 120 hours. 2 (e.g. 0.85 mg / cm 2 , 0.8mg / cm 2 , 0.75mg / cm 2 , 0.7mg / cm 2 , 0.65mg / cm 2 , 0.5mg / cm 2 , 0.4mg / cm 2 , 0.3mg / cm 2 , 0.2mg / cm 2 , 0.1mg / cm 2 ).

[0023] In a second aspect, the present invention provides a method for preparing the above-mentioned titanium alloy, comprising the following steps:

[0024] (1) Weigh the corresponding mass of raw materials;

[0025] (2) A high vacuum suspension melting furnace equipped with a water-cooled copper crucible is used for melting. After each melting is completed, the ingot is inverted and placed back into the water-cooled copper crucible for melting again. To ensure uniform composition, each ingot is melted at least four times. After the last melting is completed, casting is performed to obtain a titanium alloy casting.

[0026] The present invention adopts a high-vacuum suspension smelting furnace equipped with a water-cooled copper crucible for smelting. After each smelting is completed, the high-vacuum furnace chamber is opened to invert the ingot. The main purpose of multiple inversions and multiple smeltings is to make the titanium alloy composition more uniform and ensure that the performance of the material is stable and uniform. The casting molding preparation method has strong adaptability, the type of alloy is not restricted, and the size of the casting is almost unrestricted. Among them, sand casting is especially capable of producing parts of any complex shape, and large-sized and thin-walled parts can also be molded. Compared with the deformation processing method, it can significantly reduce manufacturing costs, and the castings can meet the use requirements of parts. The present invention adopts the casting method to carry out the molding preparation of titanium alloys to meet the development trend of large size, thin-walled curved surface, variable thickness and integrated structure of titanium alloy components. Of course, the present invention can also adopt other methods to carry out the molding preparation of titanium alloys.

[0027] Preferably, the ratio of the raw materials in step (1) adopts the mass ratio of the alloy elements.

[0028] Preferably, the raw materials described in step (1) are selected as follows: sponge titanium with a purity of 99.8%, sponge zirconium with a purity of 99.4%, Al block with a purity of 99.7%, Y block with a purity of 99.9%, Sn block with a purity of 99.9%, Mo block with a purity of 99.95%, Nb block with a purity of 99.95%, Si block with a purity of 99.5%, and Ti-90W master alloy.

[0029] Preferably, the raw materials in step (1) are designed to have a composition of 4.0-5.0% (e.g., 4.1%, 4.3%, 4.5%, 4.7%, 4.9%, 5.0%) of Al, 2.0-3.0% (e.g., 2.25%, 2.50%, 2.75%, 3.0%) of Sn, 3.0-6.0% (e.g., 3.2%, 4.0%, 5.0%, 5.8%, 6.0%) of Zr, and 0.1-1.5% (e.g., 0.3%, 0.8%, 1.2%, 1.5%) of Zr. The raw materials are preferably selected from the group consisting of 0.1% to 0.4% Mo, 0.35-0.45% (such as 0.37%, 0.4%, 0.42%, 0.45%) Si, 0.5-1.5% (such as 0.7%, 1.0%, 1.3%, 1.5%) W, 0.5-2.0% (such as 0.7%, 1.0%, 1.5%, 1.8%, 2.0%) Nb, 0.1-0.5% (such as 0.15%, 0.2%, 0.3%, 0.4%, 0.45%, 0.5%) Y, and the remainder Ti.

[0030] Specifically, a corresponding mass of raw material is weighed based on the designed alloy composition and the burnout rate of the burnout elements. The burnout rate of alloying elements is generally determined by the smelting equipment used, with similar burnout rates observed for equipment of the same model. Therefore, the elements and their burnout rates involved in the present invention can be determined based on the smelting equipment used in the present invention as follows: Al is 10% of the total Al content in the raw material, Sn is 8% of the total Sn content in the raw material, Zr is 2% of the total Zr content in the raw material, and Si is 2% of the total Si content in the raw material.

[0031] More preferably, the raw materials in step (1) are designed to have a composition of 4.2-5.0% (e.g., 4.2%, 4.5%, 4.7%, 4.9%, 5.0%) of Al, 2.65-3.0% (e.g., 2.75%, 2.85%, 2.95%, 3.0%) of Sn, 3.0-6.0% (e.g., 3.2%, 4.0%, 5.0%, 5.8%, 6.0%) of Zr, 0.6-1.5% (e.g., 0.7%, 0.8%, 1.0%, 1.2%, 1.5%) of Zr, )% Mo, 0.35-0.45% (such as 0.37%, 0.4%, 0.42%, 0.45%) Si, 0.8-1.5% (such as 0.9%, 1.0%, 1.3%, 1.5%) W, 0.5-2.0% (such as 0.7%, 1.0%, 1.5%, 1.8%, 2.0%) Nb, 0.1-0.5% (such as 0.15%, 0.2%, 0.3%, 0.4%, 0.45%, 0.5%) Y, and the balance Ti.

[0032] More preferably, the raw materials in step (1) are designed to have a composition of 4.5-5.0% (e.g., 4.6%, 4.7%, 4.8%, 4.9%, 5.0%) of Al, 2.65-2.85% (e.g., 2.7%, 2.75%, 2.8%, 2.85%) of Sn, 3.0-6.0% (e.g., 3.2%, 4.0%, 5.0%, 5.8%, 6.0%) of Zr, 0.8-1.5% (e.g., 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%) of Zr, and 0.8-1.5% (e.g., 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%) of Zr. %), 0.4-0.45% (such as 0.41%, 0.42%, 0.43%, 0.44%, 0.45%) of Mo, 0.8-1.2% (such as 0.9%, 1.0%, 1.1%, 1.2%) of W, 0.5-2.0% (such as 0.7%, 1.0%, 1.5%, 1.8%, 2.0%) of Nb, 0.1-0.4% (such as 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%) of Y, and the balance of Ti.

[0033] Preferably, in step (2), the raw materials are stacked in a water-cooled copper crucible according to their melting points, with the high-melting-point materials stacked at the bottom and the low-melting-point materials stacked at the top; the materials are stacked tightly at the bottom and loosely at the top.

[0034] By adopting the above technical solution, the raw materials are stacked according to their melting points, so that the high-melting-point materials are at the bottom and the low-melting-point materials are at the top, which can prevent the volatilization of elements during smelting; when the materials are stacked tightly at the bottom and loosely at the top, the occurrence of "bridging" during smelting can be prevented.

[0035] Preferably, in step (2), dry high-purity argon with a purity of 99.999% is used as a supplementary protective gas for alloy smelting.

[0036] When adopting the above technical solution, it should be noted that the high vacuum suspension melting furnace is in a high vacuum state before the protective gas is added. The purpose of adding the protective gas is to reduce the volatilization of active elements during melting, such as Al, Sn, Zr, Si and other elements.

[0037] Preferably, the castings made of the high-temperature, high-strength casting titanium alloy can be subjected to hot isostatic pressing during use. At the same time, different heat treatments will be performed on the titanium alloy castings according to the performance requirements of the castings.

[0038] Preferably, the hot isostatic pressing treatment is performed at a temperature of 900-1100° C., a pressure of 100-150 MPa, and a time of 1-3 h.

[0039] More preferably, the hot isostatic pressing treatment is performed at a temperature of 925° C., a pressure of 125 MPa, and a time of 2 h.

[0040] In a third aspect, the present invention provides an application of the titanium alloy described in the first aspect or the titanium alloy prepared by the preparation method described in the second aspect, which can be used for short-term high-temperature and high-strength applications.

[0041] Preferably, the short time is 0.5 to 2 hours.

[0042] Preferably, the high temperature is 700-750°C.

[0043] Preferably, the high strength is a tensile strength of not less than 600 MPa at 700°C; and a tensile strength of not less than 500 MPa at 750°C.

[0044] Preferably, the application is in the aerospace field, in particular in the outer shell of an aerospace vehicle.

[0045] More preferably, the application is a high-speed aircraft application.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] 1. The short-term high-temperature, high-strength cast Ti-Al-Sn-Zr-Mo-Si-W-Nb-Y alloy of the present invention improves the high-temperature performance of the alloy by improving the microstructure of the alloy and affecting the morphology of silicides and oxides in the alloy through the Y and Nb elements. According to the national standard GB / T 38430-2019 Corrosion of metals and alloys - Isothermal exposure oxidation test method for metal materials under high-temperature corrosion conditions, the alloy was oxidized for 120 hours at high temperatures of 700°C and 750°C, and the oxidation weight gain of the alloy sample did not exceed 0.5 mg / cm 2 and 0.9 mg / cm 2 ; According to GB / T 228.1-2021 and GB / T 228.2-2015 methods, room temperature and high temperature tensile properties tests were carried out respectively, and the results showed that the room temperature tensile strength of the alloy was not less than 1000 MPa, and the elongation was not less than 2.5%; the tensile strength at 700°C was not less than 600 MPa, and the elongation was not less than 9.0%; the tensile strength at 750°C was not less than 500 MPa, and the elongation was not less than 8.5%.

[0048] 2. The Ti-Al-Sn-Zr-Mo-Si-W-Nb-Y casting alloy of the present invention has excellent high-temperature strength at 700-750°C. Compared with the actual maximum operating temperature of 600°C for deformed titanium alloys obtained by forging or rolling methods reported at home and abroad, and the current domestic cast high-temperature titanium alloys that can only be maintained at around 450°C, it can meet the aerospace field's demand for short-term high-temperature and high-strength cast titanium alloys.

[0049] 3. The short-term high-temperature and high-strength cast Ti-Al-Sn-Zr-Mo-Si-W-Nb-Y alloy of the present invention can be used to cast some parts that are used for a short time at 700-750°C, such as the outer shell of high-speed aircraft, by pouring, injection and suction casting into the casting mold cavity, and can meet the development trend of large size, thin-walled curved surface, variable thickness and integrated structure of titanium alloy components. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 SEM images of the high-temperature, high-strength cast titanium alloys obtained in Examples 1-3: (a, b) Example 1; (c, d) Example 2; (e, f) Example 3;

[0051] Figure 2 SEM images of the high-temperature, high-strength cast titanium alloys obtained in Examples 4-6: (a, b) Example 4; (c, d) Example 5; (e, f) Example 6. DETAILED DESCRIPTION

[0052] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention.

[0053] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given. However, the protection scope of the present invention is not limited to the following embodiments. The process parameters in the following embodiments that do not specify specific conditions are generally based on conventional conditions.

[0054] The endpoints of the ranges and any values ​​disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values ​​can be combined with each other to form one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed in the present invention.

[0055] In the present invention, unless otherwise specified and / or explained, all numerical values ​​involving component amounts are "mass fractions" from beginning to end. Process parameters in the following examples where specific conditions are not specified are generally based on conventional conditions.

[0056] Since the present invention is based on laboratory preparation, the preparation process includes the following steps:

[0057] (1) Weigh the corresponding mass of raw materials;

[0058] (2) A high vacuum suspension melting furnace equipped with a water-cooled copper crucible is used for melting, and the alloy raw materials are stacked in the water-cooled copper crucible; wherein, the raw materials are stacked in the water-cooled copper crucible according to their melting points, with high melting point materials stacked at the bottom and low melting point materials stacked at the top; the materials are stacked tightly at the bottom and loosely at the top;

[0059] (3) After straightening the water-cooled copper crucible, lock and close the high vacuum suspension melting furnace door. After the furnace door is locked, open the rough pumping valve to start rough pumping in the furnace. After the rough pumping is completed, turn on the diffusion pump to start preheating;

[0060] (4) After the diffusion pump is preheated, open the main pumping valve and start evacuating the furnace. When the target vacuum degree is reached, close the main pumping valve and the diffusion pump.

[0061] (5) Then, the argon valve is opened to replenish the argon gas in the melting furnace, wherein the argon gas is selected to be dry high-purity argon gas with a purity of 99.999%;

[0062] (6) After the argon gas is replenished, open the cooling water circuit of the high vacuum suspension melting furnace;

[0063] (7) Turn on the smelting power supply, load the smelting current to 240-260A, start smelting the alloy, wait for the alloy material to be completely melted, and keep it warm for 5-10 minutes;

[0064] (8) The alloy ingot after smelting is cooled in the furnace. After the alloy ingot is cooled, the furnace door is opened, the ingot is taken out, and then the alloy ingot is inverted and placed back into the water-cooled copper crucible. Steps (3) to (7) are repeated for a second smelting. This is repeated four times. After the last smelting is completed, the alloy ingot is cast in the furnace into a round rod-shaped alloy ingot with a diameter of 60 to 100 mm (such as 60 mm, 70 mm, 80 mm, 90 mm, 100 mm).

[0065] The following will be combined with the Figure 1-2 The embodiments of the present invention are described in further detail.

[0066] The following is a clear and systematic description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without doing any substantial work are within the scope of protection of the present invention.

[0067] The materials in the following examples can all be purchased from commercial sources, and the experimental methods used therein are not specially processed.

[0068] Example 1

[0069] This embodiment provides a high-temperature, high-strength cast titanium alloy for short-term use, wherein the components include, by mass percentage, 4.5% Al, 2.75% Sn, 3.0% Zr, 1.5% Mo, 0.45% Si, 1.0% W, 2.0% Nb, 0.1% Y, and the remainder Ti and unavoidable impurities.

[0070] The preparation method comprises the following steps:

[0071] (1) Raw materials are prepared according to the designed alloy composition. The raw materials are selected as follows: 99.8% pure titanium sponge, 99.4% pure zirconium sponge, 99.7% pure Al block, 99.9% pure Y block, 99.9% pure Sn block, 99.95% pure Mo block, 99.95% pure Nb block, 99.5% pure Si block, and Ti-90W master alloy;

[0072] (2) A high vacuum suspension melting furnace equipped with a water-cooled copper crucible is used for melting, and the alloy raw materials are stacked in the water-cooled copper crucible; wherein, the raw materials are stacked in the water-cooled copper crucible according to their melting points, with high melting point materials stacked at the bottom and low melting point materials stacked at the top; the materials are stacked tightly at the bottom and loosely at the top;

[0073] (3) After straightening the water-cooled copper crucible, lock and close the high vacuum suspension melting furnace door. After the furnace door is locked, open the rough pumping valve to start rough pumping in the furnace. After the rough pumping is completed, turn on the diffusion pump to start preheating;

[0074] (4) After the diffusion pump is preheated, open the main pumping valve and start evacuating the furnace. When the target vacuum degree is reached, close the main pumping valve and the diffusion pump.

[0075] (5) Then, the argon valve is opened to replenish the argon gas in the melting furnace, wherein the argon gas is selected to be dry high-purity argon gas with a purity of 99.999%;

[0076] (6) After the argon gas is replenished, open the cooling water circuit of the high vacuum suspension melting furnace;

[0077] (7) Turn on the smelting power supply, load the smelting current to 240-260A, start smelting the alloy, wait for the alloy material to be completely melted, and keep it warm for 5-10 minutes;

[0078] (8) The alloy ingot after smelting is cooled in the furnace. After the alloy ingot is cooled, the furnace door is opened, the ingot is taken out, and then the alloy ingot is inverted and placed back into the water-cooled copper crucible. Steps (3) to (7) are repeated for a second smelting. This is repeated four times. After the last smelting is completed, it is cast into a round rod-shaped titanium alloy ingot with a diameter of 70 mm in the furnace.

[0079] The titanium alloy ingot was sampled and analyzed for composition. The results are shown in Table 1. Although impurity elements are not listed in the table, it does not mean that there are no impurity elements. The total amount of various impurities does not exceed 0.1%. Figure 1 As shown in (a) and (b) in .

[0080] Table 1 Summary of the composition of titanium alloy ingots of Examples 1-6

[0081] project element Ti Al Sn Zr Mo Si W Nb Y Example 1 Content / wt.% margin 4.5 2.75 3.0 1.5 0.45 1.0 2.0 0.1 Example 2 Content / wt.% margin 4.5 2.75 3.0 1.5 0.45 1.0 2.0 0.2 Example 3 Content / wt.% margin 4.5 2.75 3.0 1.5 0.45 1.0 2.0 0.4 Example 4 Content / wt.% margin 5.0 2.75 6.0 0.8 0.4 1.0 0.5 0.1 Example 5 Content / wt.% margin 5.0 2.75 6.0 0.8 0.4 1.0 1.0 0.1 Example 6 Content / wt.% margin 5.0 2.75 6.0 0.8 0.4 1.0 2.0 0.1

[0082] Example 2

[0083] This embodiment provides a high-temperature, high-strength cast titanium alloy for short-term use, wherein the components, by mass percentage, include: 4.5% Al, 2.75% Sn, 3.0% Zr, 1.5% Mo, 0.45% Si, 1.0% W, 2.0% Nb, 0.2% Y, and the remainder Ti and unavoidable impurities.

[0084] The preparation method is the same as that in Example 1.

[0085] The titanium alloy ingot was sampled and analyzed for composition. The results are shown in Table 1. Although impurity elements are not listed in the table, it does not mean that there are no impurity elements. The total amount of various impurities does not exceed 0.1%. Figure 1 As shown in (c) and (d) in .

[0086] Example 3

[0087] This embodiment provides a high-temperature, high-strength cast titanium alloy for short-term use, wherein the components, by mass percentage, include: 4.5% Al, 2.75% Sn, 3.0% Zr, 1.5% Mo, 0.45% Si, 1.0% W, 2.0% Nb, 0.4% Y, and the remainder Ti and unavoidable impurities.

[0088] The preparation method is the same as that in Example 1.

[0089] The titanium alloy ingot was sampled and analyzed for composition. The results are shown in Table 1. Although impurity elements are not listed in the table, it does not mean that there are no impurity elements. The total amount of various impurities does not exceed 0.1%. Figure 1 As shown in (e) and (f).

[0090] from Figure 1It can be seen that the addition of Y does not change the microstructure of the alloy, which all exhibit a Widmanstatten structure with basket weave characteristics. Furthermore, the as-cast microstructure shows relatively coarse, original β-Ti grains with large size variation. The Ti crystals are composed of lamellar α-Ti clusters and residual β-Ti phases between the lamellar phases. White particles are enriched at the prior β-Ti grain boundaries, where the white particles are Y2O3 phase. However, with increasing Y content, the alloy's microstructure tends to become more homogenous, the size variation of the original β-Ti grains decreases, and the α / β laths within the grains become thinner and shorter. The morphology of Y2O3 changes from granular to rod-like, and finally to feather-like, as the Y content increases. As the Y content increases, the distribution of the Y2O3 phase gradually shifts from primarily increasing in size to becoming more uniform. The average α / β spacings of the alloys in Examples 1, 2, and 3, calculated using the average linear intercept method based on 30 SEM images taken at different locations, were 2.17, 1.56, and 1.38 μm, respectively. The alloys in Examples 2 and 3 are 28.1% and 36.4% finer than those in Example 1, respectively. Y refines the microstructure because it has a strong electronegativity and chemical activity. It is present in the melt as an oxide during the initial solidification phase, acting as a site for heterogeneous nucleation in the melt. This pinning of grain boundaries hinders growth, increases the number of nuclei formed, and refines the alloy's grain structure.

[0091] Example 4

[0092] This embodiment provides a short-term high-temperature and high-strength cast titanium alloy, the components of which include, by mass percentage, 5.0% Al, 2.75% Sn, 6.0% Zr, 0.8% Mo, 0.4% Si, 1.0% W, 0.5% Nb, 0.1% Y, and the remainder Ti and unavoidable impurities.

[0093] The preparation method is the same as that in Example 1.

[0094] The titanium alloy ingot was sampled and analyzed for composition. The results are shown in Table 1. Although impurity elements are not listed in the table, it does not mean that there are no impurity elements. The total amount of various impurities does not exceed 0.1%. Figure 2 As shown in (a) and (b) in .

[0095] Example 5

[0096] This embodiment provides a high-temperature, high-strength cast titanium alloy for short-term use, wherein the components include, by mass percentage, 5.0% Al, 2.75% Sn, 6.0% Zr, 0.8% Mo, 0.4% Si, 1.0% W, 1.0% Nb, 0.1% Y, and the remainder Ti and unavoidable impurities.

[0097] The preparation method is the same as that in Example 1.

[0098] The titanium alloy ingot was sampled and analyzed for composition. The results are shown in Table 1. Although impurity elements are not listed in the table, it does not mean that there are no impurity elements. The total amount of various impurities does not exceed 0.1%. Figure 2 As shown in (c) and (d) in .

[0099] Example 6

[0100] This embodiment provides a high-temperature, high-strength cast titanium alloy for short-term use, wherein the components include, by mass percentage, 5.0% Al, 2.75% Sn, 6.0% Zr, 0.8% Mo, 0.4% Si, 1.0% W, 2.0% Nb, 0.1% Y, and the remainder Ti and unavoidable impurities.

[0101] The preparation method is the same as that in Example 1.

[0102] The titanium alloy ingot was sampled and analyzed for composition. The results are shown in Table 1. Although impurity elements are not listed in the table, it does not mean that there are no impurity elements. The total amount of various impurities does not exceed 0.1%. Figure 2 As shown in (e) and (f).

[0103] from Figure 2 It can be seen that the addition of Nb element does not change the alloy structure type of the alloy. The alloy structures of Example 4, Example 5 and Example 6 are all Widmanstatten structures with basket weave structure. The original β-Ti grains in the alloy structure are relatively coarse, and the size difference is obvious, ranging from 150 to 450 μm. The crystal is composed of lamellar α-Ti bundles and residual β-Ti phases between the lamellar sheets. The lamellar α-Ti and the residual β-Ti phase form an interlaced basket weave feature. The α-Ti phase and the residual β-Ti phase appear in parallel arrangement near the original β-Ti grain boundary. With the increase of Nb content, the proportion of basket weave structure in the original β-Ti phase crystal increases, and the size of the phase composition inside the grain structure first becomes smaller and then becomes larger with the increase of Nb content (such as Figure 2(b, d, f) show that a certain amount of Nb refines the microstructure, resulting in finer and shorter α-Ti lamellar clusters and interlamellar β-Ti phases. The basketweave structure exhibits significantly larger grains than the parallel-arranged structure. The average linear intercept method, calculated from 30 SEM images taken at different locations for each alloy, revealed that the average α / β stripe spacings for Examples 4, 5, and 6 were 2.27, 1.78, and 2.08 μm, respectively. The α / β stripe spacing in Example 5 was 21.6% lower than that in Example 4, while it was 16.9% higher in Example 6.

[0104] test

[0105] The titanium alloy ingots obtained in Examples 1-6 were sampled and tensile properties tested at room temperature and high temperature conditions according to GB / T 228.1-2021 and GB / T 228.2-2015 methods. The tensile strength and elongation of the titanium alloy ingots obtained in Examples 1-6 at different temperatures are shown in Table 2.

[0106] Table 2 Tensile performance test results of titanium alloy ingots of Examples 1-6 at different temperatures

[0107]

[0108] The alloy ingots from Examples 1-6 were sampled for high-temperature oxidation resistance testing according to the national standard GB / T 38430-2019, Corrosion of Metals and Alloys—Isothermal Exposure Oxidation Test Method for Metals under High-Temperature Corrosion Conditions. The alloy specimens measured 10 mm × 10 mm × 3 mm. The weight gain of the alloy specimens during oxidation reflects the alloy's resistance to high-temperature oxidation. 120-hour isothermal oxidation tests were conducted at 700°C and 750°C. The weight gain of the alloy specimens after 120 hours of oxidation at different temperatures is shown in Table 3.

[0109] Table 3 Weight gain of alloy samples of Examples 1-6 oxidized for 120 h at different temperatures

[0110]

[0111]

[0112] The Ti-Al-Sn-Zr-Mo-Si-W-Nb-Y alloys of Examples 1-6 of the present invention are prepared by adding Y and Nb elements to the Ti-Al-Sn-Zr-Mo-Si-W alloys. The combined effects of these elements affect the microstructure and structure of the alloys (e.g., Figure 1-2As shown), the alloy's operating temperature is increased, significantly improving its high-temperature strength at 700°C or higher while also taking into account its high-temperature oxidation resistance, allowing it to be used at high temperatures and strengths for a short period of time.

[0113] Through Examples 1-6, it can be seen that: Y element, as a highly chemically active element, will increase the solid solubility in titanium alloys, promote the Nb (0.143nm) and Zr (0.162nm) atoms in the alloy to replace the Ti atoms at the outer end of α-Ti (0.147nm), causing the lattice to expand in the c direction. At the same time, the solid solution of Nb and Zr elements will reduce the solid solubility of Si elements, causing the α-Ti lattice to decrease again in the a direction. The distortion of the A1 alloy is minimal, and its lattice stability is the best. The addition of Y element increases the chemical activity of the melt, reduces the melt specific interface energy σ, and thus reduces the nucleation work ΔG K , which increases the nucleation rate N, thereby making the original β-Ti grain size more uniform. The pinning effect of the Y2O3 phase enhances the strength of the grain boundary, hinders the grain boundary movement at high temperature, and improves the high-temperature performance of the alloy. In addition, the Y2O3 phase will induce the formation of parallel α / β lamellae along the grain boundary to reduce the grain distortion energy.

[0114] The addition of Nb element reduces the melt specific interface energy σ of the alloy and reduces the nucleation work ΔG K , increasing the nucleation rate N, promotes the growth of the α-Ti phase in more directions within the alloy's β-Ti grains, which is responsible for the increase in the basketweave microstructure within the β-Ti phase. Furthermore, increasing the growth direction of the α-Ti phase promotes its precipitation, thereby reducing the α / β stripe spacing and refining the alloy structure. Nb, a high-melting-point β-Ti phase-stabilizing element, has a much higher solid solubility in the β-Ti phase than in the α-Ti phase. It can hinder the movement of the original β-Ti grain boundaries, thereby hindering grain growth and refining the grains. However, the mechanisms by which Nb promotes α-Ti precipitation and hinders β-Ti growth vary depending on the Nb content. When the Nb addition is greater than 1%, its microstructure-refining effect is primarily driven by hindering β-Ti growth. When the Nb addition is less than 1%, its microstructure-refining effect is primarily driven by promoting the multi-directional growth of the α-Ti phase.

Claims

1. A short-term high-temperature high-strength casting titanium alloy, characterized in that: The titanium alloy comprises the following components in mass percentage: 4.2-5.0% Al, 2.65-2.85% Sn, 3.0-6.0% Zr, 1-1.5% Mo, 0.35-0.45% Si, 0.8-1.5% W, 0.5-2.0% Nb, 0.1-0.5% Y, and the balance Ti and unavoidable impurities; The raw materials of the titanium alloy are selected as follows: sponge titanium with a purity of 99.8%, sponge zirconium with a purity of 99.4%, Al block with a purity of 99.7%, Y block with a purity of 99.9%, Sn block with a purity of 99.9%, Mo block with a purity of 99.95%, Nb block with a purity of 99.95%, Si block with a purity of 99.5%, and Ti-90W master alloy; The room temperature tensile strength of the titanium alloy is not less than 1000 MPa, and the elongation is not less than 2.5%; The tensile strength of the titanium alloy at 700°C is not less than 600MPa; The tensile strength of the titanium alloy at 750°C is not less than 500MPa; The titanium alloy has an oxidation weight gain of no more than 0.5 mg / cm after being oxidized at 700°C for 120 hours. 2 ; The titanium alloy has an oxidation weight gain of no more than 0.9 mg / cm after being oxidized at 750°C for 120 hours. 2 .

2. The titanium alloy according to claim 1, characterized in that The titanium alloy comprises the following components in mass percentage: 4.5-5.0% Al, 2.65-2.85% Sn, 3.0-6.0% Zr, 1-1.5% Mo, 0.4-0.45% Si, 0.8-1.2% W, 0.5-2.0% Nb, 0.1-0.4% Y, and the remainder Ti and unavoidable impurities.

3. A method for preparing the titanium alloy according to any one of claims 1 to 2, comprising the following steps: (1) Weigh the corresponding mass of raw materials; (2) A high vacuum suspension melting furnace equipped with a water-cooled copper crucible is used for melting. After each melting, the ingot is inverted and put back into the water-cooled copper crucible for melting again. To ensure uniform composition, each ingot is melted at least four times. After the last melting is completed, casting is performed to obtain a titanium alloy casting.

4. The preparation method according to claim 3, characterized in that: The ratio of the raw materials in step (1) is the mass ratio of the alloy elements; And / or: In step (2), the raw materials are stacked in a water-cooled copper crucible according to their melting points, with the high melting point materials stacked at the bottom and the low melting point materials stacked at the top; the materials are stacked tightly at the bottom and loosely at the top; And / or: In step (2), the smelting uses dry high-purity argon gas with a purity of 99.999% as a supplementary protective gas for alloy smelting; And / or: The preparation method further comprises, after step (2), step (3) hot isostatic pressing, wherein the titanium alloy casting obtained in step (2) is subjected to hot isostatic pressing at a temperature of 900-1100°C, a pressure of 100-150MPa, and a time of 1-3h.

5. An application of the titanium alloy according to any one of claims 1 to 2 or the titanium alloy obtained by the preparation method according to claim 3 or 4, characterized in that: The titanium alloy is used in a high temperature environment of 700-750° C. for a short period of 0.5-2 hours.

6. The use according to claim 5, characterized in that The application is an application in the field of aerospace; And / or: the application is an application for an outer shell of an aerospace vehicle.

Citation Information

Patent Citations

  • Method for preparing titanium alloy blade by investment casting method

    CN103469009B

  • Yttrium-modified TB2 titanium alloy

    CN104404305A

  • Tungsten-containing high-strength titanium alloy

    CN105803262A

  • Multi-element solid solution strengthening heat-resistant titanium alloy

    CN105950911A

  • Polycrystalline multiphase reinforced heat-resistant titanium alloy and preparation method thereof

    CN112795811A